MODEL PENYALURAN CORPORATE SOCIALRESPONSIBILITY(CSR) PT. POLIDAYAGUNA PERKASA DI DESA. GEDANGANAK KEC. UNGARAN KAB. SEMARANG - Dimas Suryo; Wiwik Widayati; Sulityowati . (Journal of Politic and Government Studies, 2015)
Corporate social responsbility or abbreviated CSR is required in all the companies both private as well as the country, which in the Company Polidayaguna Perkasa who plays in different villages in the distribution Gedanganak Ungaran CSR is the model of partnership with NGOs since the beginning of 2014 until now. This study aims to determine why PT. Mighty Polidayaguna distribution model of CSR in partnership with NGOs PPP. The method used is interviews, literature, and documentation to the Polidayaguna Mighty, The PPP NGOs and communities receiving Party CSR is about PT. The results of the interview, studipustaka and documentation explaining the limited experience of managing CSR, time constraints and lack of expertise of PT. Polidayaguna Perkasa. Keywords: CSR, Model Distribution, PT. Mighty Polidayaguna Gedanganak village district. Ungaran